2016
DOI: 10.3390/nu8120799
|View full text |Cite
|
Sign up to set email alerts
|

Regressive Effect of Myricetin on Hepatic Steatosis in Mice Fed a High-Fat Diet

Abstract: Myricetin is an effective antioxidant in the treatment of obesity and obesity-related metabolic disorders. The objective of this study was to explore the regressive effect of myricetin on pre-existing hepatic steatosis induced by high-fat diet (HFD). C57BL/6 mice were fed either a standard diet or a HFD for 12 weeks and then half of the mice were treated with myricetin (0.12% in the diet, w/w) while on their respective diets for further 12 weeks. Myricetin treatment significantly alleviated HFD-induced steatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 48 publications
(53 reference statements)
2
34
0
Order By: Relevance
“…Indeed, our results confirmed that myricetin-treated to NASH mice effectively inhibited the activation of HSCs and hepatic fibrosis compared with vehicle-treated mice on the same diet (Figure 3). Supported our data, myricetin attenuated liver fibrosis-induced by CCl 4 in mice (29,32) and ameliorated high-fat diet-induced obesity and IR through enhancing antioxidant capacity (34). However, the exact molecular mechanisms by which myricetin exerts its beneficial effects on liver inflammation and fibrosis in NASH has been largely unknown.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Indeed, our results confirmed that myricetin-treated to NASH mice effectively inhibited the activation of HSCs and hepatic fibrosis compared with vehicle-treated mice on the same diet (Figure 3). Supported our data, myricetin attenuated liver fibrosis-induced by CCl 4 in mice (29,32) and ameliorated high-fat diet-induced obesity and IR through enhancing antioxidant capacity (34). However, the exact molecular mechanisms by which myricetin exerts its beneficial effects on liver inflammation and fibrosis in NASH has been largely unknown.…”
Section: Discussionsupporting
confidence: 70%
“…In particular, myricetin has proved to inhibit fatty acid biosynthesis and attenuate ethanol-induced lipid accumulation in liver cells (30). Furthermore, myricetin treatment also ameliorates hyperglycemia, IR, and steatosis in mouse models of obesity through antioxidant properties (33,34). These findings indicate that supplementation of the diet with myricetin might be beneficial to NASH and liver fibrosis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The degradation of starch rapidly and leads to elevation of blood glucose level. 34 on the other hand administration of ethanolic extract on alloxan induced diabetic rats, the increased level has significantly decreased. 35 Lipase is an enzyme that plays vital role in lipid metabolism which is employed in human and animal model studies.…”
Section: Histopathology Study Of Pancreas Tissuementioning
confidence: 93%
“…Therefore, mice lacking NRF2 develop more severe NASH than do wild-type mice fed a HFD [16,17]. On the other hand, HFD-or alcohol-induced downregulation of Nrf2 and its target genes contributes to the development of FLD by lowering the thresholds for the unfolded protein response and inflammation, increasing lipogenesis, and inhibiting the ability to protect against oxidative stress [18,19]. AMPK-NRF2 axis is an important intracellular signaling pathway leading to ARE-dependent transcriptional activation.…”
Section: Introductionmentioning
confidence: 99%